2014
DOI: 10.1530/erc-14-0243
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of androgen receptor signalling in breast cancer

Abstract: While the clinical benefit of androgen-based therapeutics in breast cancer has been known since the 1940s, we have only recently begun to fully understand the mechanisms of androgen action in breast cancer. Androgen signalling pathways can have either beneficial or deleterious effects in breast cancer depending on the breast cancer subtype and intracellular context. This review discusses our current knowledge of androgen signalling in breast cancer, including the relationship between serum androgens and breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 192 publications
(256 reference statements)
4
89
0
3
Order By: Relevance
“…Recently, three reviews highlighted this complexity and called No. of events for awareness when implementing AR-targeting agents in clinic practice; certain settings might require anti-androgens, whereas in other settings androgen agonists, such as selective androgen receptor modulators (30), might be warranted (8,26,31). In this study, a significant interaction between AR and ER expression with respect to DFS was found, indicating the importance of stratifying according to ER status in analyses of the prognostic value of AR.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recently, three reviews highlighted this complexity and called No. of events for awareness when implementing AR-targeting agents in clinic practice; certain settings might require anti-androgens, whereas in other settings androgen agonists, such as selective androgen receptor modulators (30), might be warranted (8,26,31). In this study, a significant interaction between AR and ER expression with respect to DFS was found, indicating the importance of stratifying according to ER status in analyses of the prognostic value of AR.…”
Section: Discussionmentioning
confidence: 63%
“…Results from clinical studies on ER À breast cancer have, however, been inconsistent, demonstrating positive or negative as well as no associations of AR with clinical outcomes (2,(18)(19)(20)(25)(26)(27). Many factors may have contributed to the reported inconsistent results; small sample sizes, heterogeneity of study populations, selection of included studies in the meta-analyses and lack of standardized methods and cutoffs for AR assessment but also for ER assessment, and the biologic heterogeneity among ER À tumors.…”
Section: Discussionmentioning
confidence: 99%
“…AR expression is higher in ER + tumors (60), with a mean expression of 74.8% in contrast to ER -tumors where it is estimated at approximately 31.8% of cases (11).…”
Section: Ar As a Potential Biomarker In Breast Tumorsmentioning
confidence: 83%
“…Androgens in breast and other female tissues Nieto et al (2014) summarise the growing evidence on the significance of AR signalling in breast development and homoeostasis in female mice, while McNamara et al (2014) and Tarulli et al (2014) focus on the emerging role of the AR in breast cancer. It has been known for decades that AR is expressed in a large proportion of breast cancers and that clinical and laboratory evidence indicated that AR signalling regulates the activity of breast cancer cells.…”
Section: Androgens and Prostate Cancermentioning
confidence: 99%
“…However, the complexity of this activity and its apparent plasticity depending on disease context has only recently been appreciated. McNamara et al (2014) summarise recent data on the complexities of AR signalling in breast cancer, including the clinical utility of assessing serum androgen levels or AR expression levels as prognostic factors in breast cancer, how ER status influences AR action in breast cancer cells and the role of AR/ER molecular crosstalk in this disease. This work is highly topical as clinical trials examining the efficacy of AR-targeting therapies (used for prostate cancer) in women with metastatic breast cancer are currently underway.…”
Section: Androgens and Prostate Cancermentioning
confidence: 99%